EVALUASI MANAJEMEN LABORATORIUM SPORT MASSAGE UNIVERSITAS BINA DARMA - Dwi Putri, Meilyn; Kesumawati, Selvi Atesya; Martinus; Melianty, Selvi (Fakultas Ilmu Keolahragaan Unimed, 2025)
ABSTRACT This study aims to evaluate the management of the Sport Massage Laboratory at Universitas Bina Darma using the CIPP evaluation model (Context, Input, Process, Product). The evaluation was conducted using a descriptive qualitative approach through observation, interviews, and documentation. The findings indicate that, in terms of context, the existence of the laboratory is highly relevant and aligned with the vision of the study program as well as the needs of the community. Regarding input, the laboratory is equipped with facilities and support staff, but there are still shortcomings in human resource management and information systems. The laboratory’s activities are running fairly well; however, the implementation of standard operating procedures (SOPs) is not yet optimal. In terms of product, the laboratory has provided tangible benefits for students, lecturers, and the general public, although there is no systematic evaluation of service outcomes in place. Overall, the laboratory management is running fairly well but requires improvements in several aspects. Therefore, it is recommended to enhance staff competence through training, develop a more organized management system, conduct regular service evaluations, and increase promotion efforts to make the laboratory more recognized and utilized optimally. Keywords: evaluation, management, laboratory, sport massage, CIPP